2020
DOI: 10.1002/lsm.23280
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Optical Coherence Tomography Imaging of Telangiectasia Prior to Intense Pulsed Light Treatment—An Opportunity to Target Treatment?

Abstract: Background and Objectives To investigate whether optical coherence tomography (OCT) could be utilized to characterize blood flow and vessel dimensions of facial telangiectasias before and during consecutive intense pulsed light (IPL) treatment. Study Design/Materials and methods Dynamic OCT (D‐OCT) was used to image telangiectasia immediately before and after, 1–3 days after, and 1 month after IPL treatment. Measurements included vessel width and depth, blood flow, and attenuation. Vessel dimensions at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…However, all of these have very limited results, if any, and there have been no large‐scale studies proving their long‐term efficacy for this condition. Considering IPL is used to decrease postprocedural purpura [28,32], is associated with a significantly altered expression of RNAs similar to that in youthful skin [37], decreases superficial telangiectasia [27], and increases collagen production and epidermal thickening [20], it appears to be an ideal option for the treatment and prevention of senile purpura.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, all of these have very limited results, if any, and there have been no large‐scale studies proving their long‐term efficacy for this condition. Considering IPL is used to decrease postprocedural purpura [28,32], is associated with a significantly altered expression of RNAs similar to that in youthful skin [37], decreases superficial telangiectasia [27], and increases collagen production and epidermal thickening [20], it appears to be an ideal option for the treatment and prevention of senile purpura.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies utilizing IPL for rosacea have shown a clinically significant reduction in telangiectasia and redness [25,26] and improvement in skin texture [26]. In fact, a study directly analyzing telangiectasias has shown that superficial telangiectasias were preferentially reduced with IPL on analysis with dynamic optical coherence tomography (D‐OCT) [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Better visualization of blood flow and vessel dimensions may help to improve the results of treatment with IPL [35].…”
Section: Iplmentioning
confidence: 99%
“…Zum Beispiel zeigte sich die D-OCT dafür geeignet, die Verengung und Verdün-nung der Blutgefäße nach der lokalen Behandlung der Rosazea mit dem α-2-adrenergen Rezeptoragonist Brimonidin zu erfassen [27]. Im Fall von Teleangiektasien im Gesicht konnte festgestellt werden, dass diese sich nach einer Behandlung mit "intense pulsed light" (IPL) tiefer in die Haut zurückzogen, was darauf hindeutet, dass eine routinemäßige IPL-Behandlung in erster Linie auf die oberflächlichsten Gefäße wirkt [28]. Die D-OCT-Bildgebung könnte insofern in der IPL-Nachbehandlung gezielt eingesetzt werden.…”
Section: Teleangiektasienunclassified